2021
DOI: 10.3390/mi12030293
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Photopolymerized Microparticles Based on PEGDA Using Microfluidic Devices. Part 1. Initial Gelation Time and Mechanical Properties of the Material

Abstract: Photopolymerized microparticles are made of biocompatible hydrogels like Polyethylene Glycol Diacrylate (PEGDA) by using microfluidic devices are a good option for encapsulation, transport and retention of biological or toxic agents. Due to the different applications of these microparticles, it is important to investigate the formulation and the mechanical properties of the material of which they are made of. Therefore, in the present study, mechanical tests were carried out to determine the swelling, drying, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The swelling ratio calculated from Equation (2) increased from 0.36 to 0.60 as the water content in the PEGDA solution before polymerisation increased from 10 wt% to 40 wt%. The density of pure PEGDA in these calculations was assumed as ρ p = 1.18 g/cm 3 [54]. The increase in swelling ratio with an increase in water content in a PEGDA prepolymer solution was observed in other studies.…”
Section: Impact Of Water Content In the Dispersed Phase On Shrinkage/...mentioning
confidence: 70%
“…The swelling ratio calculated from Equation (2) increased from 0.36 to 0.60 as the water content in the PEGDA solution before polymerisation increased from 10 wt% to 40 wt%. The density of pure PEGDA in these calculations was assumed as ρ p = 1.18 g/cm 3 [54]. The increase in swelling ratio with an increase in water content in a PEGDA prepolymer solution was observed in other studies.…”
Section: Impact Of Water Content In the Dispersed Phase On Shrinkage/...mentioning
confidence: 70%
“…This phenomenon is attributed to the addition of OA segments to the PEGDMA matrix, which increased the intermolecular distance between the polymer chains of PEGDMA, thereby reducing the cross-linking network density of the copolymer. ,,,,,, The OA-PEG copolymer with a lower cross-linking density exhibited enhanced water absorption and dispersion. According to previous studies, an increase in the hydrogel swelling ratio indicates an increased distance between the polymer chains and a lower cross-linking density. To analyze the swelling behaviors, the weights of the PEGDMA and 5 wt % OA-PEG samples were measured after water immersion of the samples for 18 h. The swelling ratios of the 1, 3, and 5 wt % OA-PEG samples were 28.8 ± 1.3, 31.5 ± 1.5, and 34.3 ± 1.5%, respectively, whereas the swelling ratio of PEGDMA was only 24.2 ± 1.7% (Figure S8). This result demonstrated that the intermolecular distance of the OA-PEG copolymer increased with increasing OA content in the OA-PEG copolymer.…”
Section: Resultsmentioning
confidence: 91%
“…Microfluidics provides a new approach to prepare multi‐component double emulsion droplets, where the encapsulated droplets' composition, number, and size can be precisely and independently controlled. Microemulsion droplets can be solidified through various methods, including polymerization reactions, cross‐linking reactions, phase separation, and self‐assembly [23–26] . Polymerization is the most widely used method due to its broad applicability, high curing efficiency, and numerous polymeric materials available.…”
Section: Introductionmentioning
confidence: 99%
“…Microemulsion droplets can be solidified through various methods, including polymerization reactions, cross-linking reactions, phase separation, and self-assembly. [23][24][25][26] Polymerization is the most widely used method due to its broad applicability, high curing efficiency, and numerous polymeric materials available. The conversion process can typically be achieved by adding a photosensitive prepolymer into the dispersed phase, with a small amount of initiator, under heating or UV irradiation conditions.…”
mentioning
confidence: 99%